LEVERAGING TRUST: YOUTUBE ENTERTAINERS AND THE ROLE OF PROBLEM-SOLVING IN ENGENDERING TRUST. - Healy, Guy Hamilton (AoIR Selected Papers of Internet Research, 2019)
This paper aims to better understand the role that problem-solving plays in building the trust necessary to sustain online fan audiences, and so support the careers of influential social media entertainers. Problem-solving in this context means a video, where the theme deals with the problems of modern life experienced by young fans. A mixed methods approach – in this case in-depth interviews, discourse analysis and participant observation at YouTube Creator Day events – is used to better leverage the strengths of each method and triangulate results. Sample size is at least 20 YouTubers at the most culturally significant, artistic end of the spectrum with an average of at least 1mn subscribers, established TV producers and Multi-Channel Network leaders. Preliminary results suggest that leading YouTube creators – including A-listers – use a conscious strategy of identifying the problems fans experience, so establishing trust and building audiences for their videos around their own solutions. Moreover, trust is engendered through two main means say these Australian YouTubers: first, the considerable time creators spend listening to their fans across creators’ YouTube, Twitter, Facebook and Patreon channels; and second, via online and analogue interactions with fans that open their lifeworld’s to the creator, and in turn shape the themes of their short video products. This phenomenon of collaborative problem-solving, independent of traditional state, school or family structures, represents an important shift with significant potential for youth agency in an emergent public sphere.